2022
DOI: 10.1186/s12941-022-00526-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determination of O25b/ST131 clone type among extended spectrum β-lactamases production Escherichia coli recovering from urinary tract infection isolates

Abstract: Background Escherichia coli (E. coli) O25b/ST131 clone causes urinary tract infection (UTI) and is associated with a broad spectrum of other infections, such as intra-abdominal and soft tissue infections, that can be affecting bloodstream infections. Therefore, since O25b/ST131 has been reported in several studies from Iran, in the current study, we have investigated the molecular characteristics, typing, and biofilm formation of O25b/ST131 clone type E. coli collected from UTI specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Of the 86 isolates, 73% showed a weak relationship; however, the rest of the isolates were not related, indicating the absence of specific outbreaks due to the presence of multiple groups. The aforementioned findings are comparable to those in Iran, where 14 groups were identified in the clonal relationship analysis of uropathogenic E. coli (28). Similarly, a study in Romania identified 13 groups with a 75% similarity; nevertheless, Ecuador exhibited extensive genetic diversity among these strains, resulting in more than 30 groups (29,30).…”
Section: Discussionsupporting
confidence: 79%
“…Of the 86 isolates, 73% showed a weak relationship; however, the rest of the isolates were not related, indicating the absence of specific outbreaks due to the presence of multiple groups. The aforementioned findings are comparable to those in Iran, where 14 groups were identified in the clonal relationship analysis of uropathogenic E. coli (28). Similarly, a study in Romania identified 13 groups with a 75% similarity; nevertheless, Ecuador exhibited extensive genetic diversity among these strains, resulting in more than 30 groups (29,30).…”
Section: Discussionsupporting
confidence: 79%
“…This clone carries the β-lactamase gene, bla CTX-M [59]. In addition, some strains might carry bla TEM [60,61], bla SHV [61,62], ampC [60], or other genes [60]. In the strains of this clone, CTX-M is usually coproduced with OXA-1 and an aminoglycoside-modifying enzyme encoded by the aac(6 )-Ib-cr gene that confers resistance to aminoglycosides and fluoroquinolones [55,63].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 150 million Urinary Tract Infections (UTIs) are reported annually worldwide, and drug-resistant infections usually require more complex treatment regimens and are more likely to occur if treatment fails ( Khoshbayan et al., 2022 ). NF is outstanding because NF is most extensively utilized in humans, and its effectiveness in the treatment of lower UTIs and prophylaxis is well established ( Conklin, 1978 ).…”
Section: Introductionmentioning
confidence: 99%